An unexpected method to synthesise 1, 2, 4-oxadiazolone derivatives: a class of insensitive energetic materials. (14th November 2018) - Wang, Bohan; Xiong, Hualin; Cheng, Guangbin; Zhang, Zaichao; Yang, Hongwei
Abstract : A new and effective method for the preparation of 3-(4-amino-1, 2, 5-oxadiazol-3-yl)-1, 2, 4-oxadiazol-5(4 H )-one is presented. Explosophore groups such as NO2 NH–, NO2 –, C(NO2 )3 CH2 NH– and –NN– were incorporated by a variety of functionalization strategies. Abstract : A new and effective method for the preparation of 3-(4-amino-1, 2, 5-oxadiazol-3-yl)-1, 2, 4-oxadiazol-5(4 H )-one is presented. In order to develop high energy density materials, compounds3, 4 and6 were synthesized by the simple nitration, oxidation and oxidation coupling reaction of compound2 . In addition, six energetic salts based on3 and4 were synthesized, respectively. Compounds2–12 were characterized by IR spectroscopy, multinuclear NMR spectroscopy and elemental analysis. The structures of compounds2, 4 and7 were determined by single crystal X-ray diffraction. In addition, the energetic properties of compounds3–12 including density (1.60–1.88 g cm −3 ), thermal stability (161.83–315.75 °C), except compound3 which decomposed at 127.25 °C, and sensitivity were also investigated. The energetic performance ( P : 22.25–35.81 GPa; D : 7749–8892 m s −1 ) from the experimental densities and calculated heats of formation suggests that many of them have potential applications as energetic materials.